Pengaruh metode penilaian persediaan terhadap volatilitas return on asset, volatilitas cost of sale, dan volatilitas profit or loss pada perusahaan real estate dan properti yang tercatat di bursa efek indonesia periode 2007 - 2009 - Ngadiman Ngadiman; Lydiawati Santoso (Jurnal Akuntansi, 2013)
The purpose of this study is to investigate the influence of inventory evaluation method toward ROA volatility, cost of sale volatility, and profit or loss volatility in publicly listed real estate and property companies in Indonesian Stock Exchange related to valuation method decision which more describes current cost. This study uses data from 34 samples during year 2007 – 2009. It is an empirical study using regression model with dummy variable. Therefore, before conducting hypothesis testing, the classic assumption testing was done. Beside that, t-test was done and shows there is significant average difference of profit or loss volatility in company using average method and FIFO method. The results show that: Inventory valuation method has significant influence toward profit or loss volatility. But, inventory valuation method doesn’t have significant influence toward ROA and cost of sale volatility using 95% level of confidence. For further studies, it is expected to use longer observation period and other variables to minimize bias that might happen.